Potential phages against Vibrio alginolyticus from oyster and clams - Zin, Ain-Auzureen Mat; Ying, Lee Rui; Peng, Tan Li; Mohamed, Maizan; Afifah Moh, Nora Faten; Hamid, Nur Hidayahanum; CheWan Zal, CheWan Salma; Samsuddin, Ahmad Syazwan; Hamdan, Ruhil Hayati (Science Alert, 2024)
Background and Objective: Vibriosis is a disease that causes massive mortality in aquaculture farming in Asia which is commonly controlled by antibiotics. Increasing Antimicrobial Resistance (AMR) in Vibrio species may lead to bacteriophage therapy as an option for fish farmers to treat vibriosis. The objective of this study was to isolate and identify bacteriophage from bean clam, carpet clam and wild oysters against Vibrio alginolyticus strains. Materials and Methods: The 30 bivalve samples including 10 each for bean clams, carpet clams and wild oysters were purchased from local and street wet markets around Pengkalan Chepa and Bachok, Kelantan. Spot tests and plaque formation were done to isolate the phages from bivalve molluscs. Then, the isolated phages were identified morphologically using a Transmission Electron Microscope (TEM). Results: The two isolates of phages were isolated from white oysters (VA-WO1) and carpet clams (VA-CC1). Unfortunately, only the VA-WO1 phage was further studied due to technical errors. Morphologically the bacteriophage identified using TEM belongs to the Siphoviridae family. The VA-WOI phage only targeted specific strains of Vibrio alginolyticus (K5). Conclusion: Further studies are needed to isolate other phages for effective vibriosis treatment. Thus, the obtained phages will further characterize the molecular and genome sequences examination. Phages have a huge potential to become supportive tools development of antibiotic treatment.